2006
DOI: 10.1037/0012-1649.42.6.1179
|View full text |Cite
|
Sign up to set email alerts
|

Class climate moderates peer relations and emotional adjustment in children with an early history of anxious solitude: A child × environment model.

Abstract: Classroom emotional climate was hypothesized to moderate psychosocial adjustment in 1st grade for children with an early childhood history of anxious solitude. Participants were 1,364 children in the National Institute of Child Health and Human Development (NICHD) Study of Early Child Care and their mothers, child-care providers, and teachers. As anticipated, children with an early childhood history of anxious solitude were more rejected, poorly accepted (boys), and victimized (girls) by peers and demonstrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
167
3
18

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 170 publications
(201 citation statements)
references
References 48 publications
13
167
3
18
Order By: Relevance
“…We frame risk for peer adversity as a function of both child and environment. Previous work supports the importance of the concurrent environment in which peer adversity takes place; children with an early childhood history of anxious solitude were more likely to become rejected in first grade if their classrooms were characterized by a negative emotional climate at school (Gazelle, 2006). In the present investigation, we examine whether individual and relational factors that predate school entry contribute to differential success with peer relationships.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…We frame risk for peer adversity as a function of both child and environment. Previous work supports the importance of the concurrent environment in which peer adversity takes place; children with an early childhood history of anxious solitude were more likely to become rejected in first grade if their classrooms were characterized by a negative emotional climate at school (Gazelle, 2006). In the present investigation, we examine whether individual and relational factors that predate school entry contribute to differential success with peer relationships.…”
Section: Introductionmentioning
confidence: 86%
“…Convergence was expected to be modest because mothers and child care providers observe children in different contexts (Achenbach, McConaughy, & Howell, 1987). Child care provider rather than maternal reports are employed as predictors because previous work has demonstrated that child care provider reports of anxious solitude have superior predictive validity in relation to children's social functioning at school (Gazelle, 2006).…”
Section: Primary Predictor Variablesmentioning
confidence: 99%
“…Not all shy children, however, display such patterns, and research findings examining teacher-child relationships indicate that shy children, in addition to interacting less overall, also tend to engage in less conflict with teachers (Rudasill & Rimm-Kaufman, 2009). Further empirical evidence suggests that teachers who show more sensitive teaching styles and behaviors and/or create more sensitive classrooms may provide a supportive context for withdrawn children that can ameliorate the link between shyness and poorer school adjustment (Avant, Gazelle, & Faldowski, 2011;Gazelle, 2006;Pianta, 1999). Teachers who are consistently warm, positive, and respond appropriately to children's cues may also help children develop better self-regulation and autonomous classroom behaviors-skills that are likely to benefit shy children in particular (Arbeau, Coplan, & Weeks, 2010;Pianta, La Paro, Payne, Cox, & Bradley, 2002).…”
Section: Temperament Peers and Adjustmentmentioning
confidence: 99%
“…교사는 부모와 마찬가지로 유아에게 자신의 주변 환경을 적극적이고 유능하게 탐색할 수 있는 안전 기지의 역할을 하며 (DeMuller et al, 2000), 기관생활에서 필요 한 대처 기술을 가르친다 (Doll, 1996) [ .88, 교사-유아 갈등 관계 .85이었다. (Arbeau et al, 2010;Birch & Ladd, 1997;Gazelle, 2006;Hamre & Pianta, 2001;Hughes et al, 2008;Pianta, 1994 …”
Section: 한국생활과학회지 제22권 3호 2013unclassified